Corneal Complications During and After Vitrectomy for Retinal Detachment in Photorefractive Keratectomy Treated Eyes. Issue 50 (December 2015) - Tosi, Gian Marco; Baiocchi, Stefano; Balestrazzi, Angelo; Martone, Gianluca; Marigliani, Davide; Neri, Giovanni; Caporossi, Tomaso
Abstract : Abstract: To evaluate the occurrence of late-onset corneal haze (LOCH) after vitrectomy for rhegmatogenous retinal detachment (RRD) in photorefractive keratectomy (PRK)-treated eyes. This observational cohort study comprised 13 eyes of 13 patients who underwent vitrectomy for RRD and who had been subjected to PRK years earlier. The occurrence of LOCH was evaluated together with all the preoperative, intraoperative, and postoperative factors that could affect final corneal status. LOCH developed in 2 eyes. Both patients had undergone PRK for high myopia—one 3 years and the other 9 years prior to RRD. Both patients presented with RRD due to giant retinal tear and were subjected to scleral buckle, 20-gauge vitrectomy, and silicone oil tamponade. Three months after vitrectomy and 1 month after silicone oil removal they both developed LOCH. During vitreoretinal surgery neither of the 2 patients needed mechanical epithelial debridement. Intraoperative epithelial debridement was performed in 2 of the other patients of the series, who had undergone previous PRK for high myopia and had clear corneas at presentation; in 1 of them this manoeuvre hampered intraoperative visualization. Follow-up after retinal detachment surgery ranged from 6 to 156 months (mean, 37.5 months). Subepithelial corneal scarring may be reactivated many years after PRK. In our series this happened after vitrectomy.